Positive solutions to a nonlinear eigenvalue problem of fractional differential equation with integro-differential boundary conditions (2017)
In this paper, we establish the existence of positive solutions for eigenvalue problem of fractional differential equations with integro-differential boundary conditions. We determine the intervals of parameter _ for which the existence of positive solutions is guaranteed. An example is also presented to show the application of our results.